RANCANG BANGUN SISTEM PENGIRIMAN BERKAS BERMASALAH BERBASIS ONLINE DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN LOMBOK TIMUR - Permana, Baiq Andriska Candra; Fatthuriadi, Fatthuriadi; Ahmadi, Hamzan (Fakultas Teknik Universitas Hamzanwadi, 2020)
During this time, the process of sending files between the Department of Population and Civil Registration with Technical Implementation Unit is still using a manual system, it makes the process of resolving problematic files has been slow which has an impact on public dissatisfaction to government services. This study aims to assist the local office in overcoming these problems by utilizing existing internet networks and building an online-based system for sending the problem files. This research using waterfall method to develop software systems by having an ordered software life path that starts from analysis, design, coding and testing. With an online-based system, file transfers can be done quickly and the number of problem files can be recorded automaticallyDOI : 10.29408/jit.v3i1.1792